A CASE REPORT: UNILATERAL COMPLETE CLEFT LIP RECONSTRUCTION USING THE MODIFICATION MILLARD TECHNIQUE - Theodora Ratih Labdagati Iswara; Muhammad Aulia Ul Hakim (Jurnal Rekonstruksi dan Estetik, 2023)
Highlights: The modified Millard technique, including the Tennison triangular flap, is effective in preventing vermillion notching and reducing scar complications in cleft lip repairs. The technique addresses concerns related to compromised lip tissue and nostril deformities, leading to improved appearance and functionality. Scar thinning techniques and separate nasoraphy contribute to enhanced aesthetics and optimal healing in cleft lip repairs. Abstract: Introduction: With 1 in 700 live births worldwide, cleft lip with or without cleft palate is the most prevalent congenital craniomaxillofacial birth condition. More people have a unilateral cleft lip than a bilateral cleft lip. With the exception of vision, it can influence the morphology and nearly all facial functions. The purpose of this study is to give an overview and learn more about the management of lip repair using the modified Millard approach, which can prevent straight line closure and vermilion notching. Case Illustration: We present a case of a 4-month-old male who underwent a modified Millard procedure and had a unilateral full cleft lip. The findings revealed no vermillion notch, acceptable columellar and alar lengths, symmetrical Cupid's bow, lip height, lip width, and philtrum angle. Discussion: The modified Millard technique, including the Tennison triangular flap, improves the repair of cleft lips by preventing vermillion notching and reducing scar complications. It also addresses concerns related to lip tissue compromise and nostril deformities. Scar thinning techniques and separate nasoraphy contribute to enhanced aesthetics and optimal healing. These modifications aim to achieve improved appearance and functionality in cleft lip repairs. Conclusion: The modified Millard technique can be considered as a viable option for treating unilateral cleft lip due to its ability to create a balanced Cupid's bow, maintain appropriate lip height and width, and achieve satisfactory aesthetic results in the nasal area without vermillion notching.